Inflation threshold and nonlinearity: implications for inflation targeting in South Africa - Morar, Derwina (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2011)
Following many other central banks around the world, the South African Reserve Bank has adopted inflation targeting as its monetary policy framework. The aim of this is to achieve low levels of inflation in order to attain price stability thereby promoting growth. In South Africa, the chosen band to target is 3%"“6%. This has been criticised by many trade unions who are calling for the abandonment of inflation targeting. Despite targeting 3%"“6%, it is not known whether this is the optimal inflation range for South Africa. Therefore, the aim of this study is to determine the inflation threshold level for South Africa using quarterly data for the period 1983 to 2010. The first section determines whether or not there is a long-run relationship between inflation and growth using the Johansen cointegration method. Exogeneity tests determine the causality between these variables. Vector error correction models are estimated if cointegration is found. The second part determines the threshold level of inflation using the method of conditional least squares. The inflation level that maximises the R-squared value and minimises the residual sum of squares gives an indication of the threshold level. The third part of the study determines whether or not inflation volatility has a significant impact on growth. The first part established that there is long-run comovement between inflation and growth.The causality is bidirectional with both variables being endogenous.Findings regarding the threshold level show that the current inflation targeting band of 3%"“6% may be extended up to 9.5%. In addition, the range of inflation from 5.5% to 6.5% promotes economic growth in South Africa. Finally, the evidence suggests that inflation volatility does not have a significant impact on economic growth and the focus of policy should be directed towards the level of inflation as has been the case.
Keywords: Inflation targeting -- South Africa; Interest rates -- Effect of inflation on -- South Africa; Monetary policy -- South Africa; Economic development -- South Africa